Prof. Dr. José Pereira de Queiroz Neto - Leader in the study of the relationships between Pedology and Geomorphology in Brazil - Castro, Selma Simões de; Ferreira , Rosely Pacheco Dias; Espíndola, Carlos Roberto; Pinheiro, Marcos Roberto (Revista Brasileira de Geomorfologia, 2025)
This text discusses the research, teaching and extension activities developed by Prof. Dr. José Pereira de Queiroz Neto, who left us on May 26, 2024, at almost 95 years old. It is noteworthy that as a professor at the Department of Geography at the University of São Paulo, founder and coordinator of the Pedology Laboratory at that same institution, he led numerous research and teaching at undergraduate and mainly postgraduate levels regarding the relationships between pedogenesis and morphogenesis, valuing especially the level of slopes in small river basins. Furthermore, he coordinated several scientific and teaching cooperation programs with France, through which he developed several important partnerships with other leaders in these areas.